Mechanisms of Secondary Bacterial Infections in Viral Infections - Harshini T Reddy; Bhaskar Shenoy (Pediatric Infectious Disease)
Secondary bacterial infections most commonly occur post-viral or concomitant with viral infections. Viral infections damage both innate and acquired immune systems which facilitates bacterial adhesion, growth and invasion of healthy sites of body. These secondary bacterial infections lead to more severe clinical course and worsen the prognosis of the infection. Viral infections alter the commensal microbiota leading to dysbiosis which in turn predisposes to secondary bacterial infections. This review article elaborates the underlying mechanisms of secondary bacterial infections which will lead us to develop novel and therapeutic approaches towards prevention and treatment of secondary bacterial infection which plays a vital role in improving clinical outcome.